Lohnspreizung und Arbeitslosigkeit : theoretische Erklärungsansätze und Stand empirischer Forschung - Simone Kohnz; Georg Erber (Deutsches Institut für Wirtschaftsforschung (DIW), 2000)
[Inhaltsverzeichnis] 1. Lohnspreizung - Ein gesellschaftspolitisches Problem 2. Theoretische Erklärungsansätze zur Lohnspreizung 2.1. Einfaches Arbeitsmarktmodell mit homogenen Arbeitsangebot 2.2. Einfaches Arbeitsmarktmodell mit heterogenen Arbeitsangebot 2.3. trade-off-Hypothese zwischen Arbeitslosigkeit und Lohnspreizung 3. Einlußfaktoren der Lohnspreizung 3.1. Marktbestimmte Faktoren 3.1.1. Faktoren der Nachfrageseite 3.1.2. Faktoren der Angebotsseite 3.2. Institutionelle Faktoren des Arbeitsmarktes 4. Stand der empirischen Forschung zur Lohnspreizung in den USA 4.1. Quantitativer Einfluß der Nachfrage- und Angebotsfaktoren 4.2. Quantitativer Einfluß der institutionellen Faktoren 4.3. Besondere Entwicklung der Arbeitseinkommen von Frauen 5. Entwicklungen in Deutschland 5.1. Entwicklung der Lohngleichheit 5.2. Trade-off zwischen Arbeitslosigkeit und Lohnspreizung 6. Gestaltungsmöglichkeiten und Wirtschaftspolitische Handlungsoptionen 7. Ausblick – – The origin of increasing income inequality and strategies to influence this unwarranted development has stimulated major debates during the 1990s under economists, politicians and the general public in a number of OECD countries and the U.S. in particular. While this topic includes a broader agenda the focus of our paper is on possible sources of increasing wage inequality. The paper summarizes major theoretical arguments to explain these developments based on a simple comparative static model of the labor market with two inputs, skilled and unskilled labor. Current theories of labor markets identify demand and supply shifts and institutional factors affecting the income dispersion. Skill-biased technological change and trade liberalization are recognized as the major drivers of demand shifts. While these demand shifts tend to rise income inequality, the increasing supply of skilled workers influences income in the opposite direction. A third set of institutional factors influence wage dispersion like e.g. minimum wages or unionization as well as labor market legislation or other labor market regulations. These institutional factors tend to influence functional wage inequality compared to a pure competitive market solution. However institutional arrangements normally do not attempt to clear labor markets and therefore implicitly contribute to unemployment. The low level of unskilled unemployment as well as of unemployment in general in the U.S. during the 1990s compared to continental Europe and Germany in particular has lead to the statement of the trade-off hypothesis by Krugman that the high unemployment in Europe is just the other side of the medal where increasing wage inequality is subdued by institutional arrangements. This hypothesis is controversially discussed by other authors because of contradicting or inconclusive empirical evidence. Increasing wage inequality might bring down unemployment in Europe but will contribute on the other hand to phenomena like the working poor in the U.S. While this dilemma cannot be overcome following the trade-off hypothesis it is a more promising strategy in the long-run to focus economic policy responses to improve the supply side conditions for skill formation. By summing up empirical research results on this issue for the U.S. and Germany the authors attempt to assess to what extent these theoretical explanation are sufficient to give an appropriate account what is observed in reality.
Keywords: J31; 330; Lohnstruktur; Arbeitsmarkttheorie; Arbeitslosigkeit; Theorie; Deutschland; Vereinigte Staaten